Safety and efficacy of dual PI3K-δ, γ inhibitor, duvelisib in patients with relapsed or refractory lymphoid neoplasms: A systematic review and meta-analysis of prospective clinical trials - Wang, Zhongwang; Zhou, Hui; Xu, Jing; Wang, Jinjin; Niu, Ting (Frontiers in Immunology, 2023)
Background: Duvelisib is the first FDA-approved oral dual inhibitor of phosphatidylinositol-3-kinase PI3K-delta (PI3K-δ) and PI3K-gamma (PI3K-γ). Although many clinical studies support the efficacy of duvelisib, the safety of duvelisib remains with great attention. This systematic review and meta-analysis aimed to evaluate the safety and efficacy of duvelisib in treating different relapsed or refractory (RR) lymphoid neoplasm types. Methods: We searched prospective clinical trials from PUBMED, EMBASE, Cochrane Library, and ClinicalTrials.gov. For efficacy analysis, Overall response rate (ORR), complete response rate (CR), partial response rate (PR), rate of stable disease (SDR), rate of progressive disease (PDR), median progression-free survival (mPFS), 12-/24-month PFS, and 12-month overall survival (OS) were assessed. For safety analysis, the incidences of any grade and grade ≥3 adverse events (AEs), serious AEs, and treatment-related discontinuation and death were evaluated. Subgroup analysis according to the disease type was performed. Results: We included 11 studies and 683 patients, including 305 chronic lymphocytic leukemia/small lymphocytic lymphoma (CLL/SLL), 187 B-cell indolent non-Hodgkin lymphoma (iNHL), 39 B-cell aggressive non-Hodgkin lymphoma (aNHL), and 152 T-cell non-Hodgkin lymphoma (T-NHL) patients. The pooled ORR in CLL/SLL, iNHL, aNHL and T-NHL was 70.0% (58.9-81.1%), 70.2% (47.5-92.9%), 28.2% (14.1-42.3%) and 46.7% (38.7-54.6%), respectively. Additionally, the pooled ORR in CLL/SLL patients with or without TP53 mutation/17p-deletion (62.0% vs. 74.1%, p=0.45) and in follicular lymphoma (FL) or other iNHL (69.3% vs. 56.6%, p=0.38) had no significant differences. Mantle cell lymphoma (MCL) patients had higher pooled ORR than other aNHL (67.9% vs. 17.0%, p=0.04). Angioimmunoblastic TCL (AITL) patients had higher pooled ORR than other PTCL patients (66.7% vs. 41.7%, p=0.01). The pooled incidence of any grade, grade ≥3, serious AEs, treatment-related discontinuation and death was 99.2% (98.2-100%), 79.4% (67.4%-91.4%), 63.1% (52.6-73.7%), 32.6% (24.6%-40.7%) and 2.7% (1.4%-4.3%), respectively. The most frequent any-grade AEs were diarrhea (47.3%), ALT/AST increase (38.9%), and neutropenia (38.0%). The most frequent grade ≥3 AEs were neutropenia (25.1%), ALT/AST increased (15.6%), diarrhea (12.3%), and anemia (11.9%). Conclusion: Generally, duvelisib could offer favorable efficacy in patients with RR CLL/SLL, iNHL, MCL, and AITL. Risk and severity in duvelisib treatment may be mitigated through proper identification and management.